Particle Tracking in Fluidized Beds with Secondary Gas Injection - Hensler, Timo; Tupy, Martin; Strer, Timo; Pöschel, Thorsten; Wirth, Karl-Ernst (Procedia Engineering, 2015)
Fluidized beds with secondary gas injection enjoy great popularity in process industry. Owing to their characteristic properties such as intense mixing of solids, excellent mass and heat transfer conditions as well as easy handling of solids, this type of apparatus is applied in various fields of process engineering nowadays. In the past decades research concerning fluidized beds with secondary gas injection has focused on understanding how solid particles and the injected gas are distributed within the apparatus. With the aid of invasive measurement techniques the region surrounding the injector nozzle was investigated with respect to the penetration depth of the gas jet above the nozzle orifice as well as the jet opening angle. A major drawback of the previously used measurement techniques consists in their invasive nature. Penetration of the injection zone by a probe can severely influence the local flow pattern and consequently has a detrimental effect on the reliability of the measured data. Therefore in the presented work for the first time the solids distribution as well as the motion of a single particle in a fluidized bed with secondary gas injection has been investigated by positron emission particle tracking (PEPT). This non-invasive technique is based on labeling one single particle, randomly selected from the bulk, radioactively, which allows for tracking its motion with high temporal and spatial resolution. The obtained data are compared with results derived from invasive measurements. Moreover PEPT-data have been used to perform investigations on the residence time behavior of particles within the jet region and the suspended phase. It could be found that the combination of invasive measurements and PEPT provide valuable information for the design and optimization of fluidized bed reactors with a well-defined injection zone.
EAM Import::2019-03-08